Quantification of TP73 gene transcripts in acute promyelocytic leukemia and its impact on prognosis and treatment response - Ortiz Rojas, César Alexander (2022)
Currently, acute promyelocytic leukemia (APL) is treated with all-trans retinoic acid (ATRA) associated with anthracyclines or arsenic trioxide (ATO). Unfortunately, some patients relapse or are refractory to treatment. Lucena-Araújo et al. (2015) demonstrated that high values of the ratio between the number of transcripts of the ΔNp73 and TAp73 isoforms of the TP73 gene are associated with a worse treatment outcome in patients with APL. Here we expand the knowledge about the association of p73 isoforms and prognosis in APL, exploring possible mechanisms in the response to ATRA and ATO. We evaluated the expression levels of TAp73, ΔNp73, TP73α and TP73β in public databases containing information on the transcriptome of patients with APL, and we also quantified the respective transcripts in samples at diagnosis of patients who were part of the IC-APL study. Compared with healthy bone marrow cells, we detected lower expression of TAp73 and higher expression of ΔNp73 and TP73β in APL samples. High ΔNp73 expression was associated with lower overall survival (OS) rates (Log rank, p = 0.023), but not disease-free survival. At 5 years of follow-up, patients with high expression of ΔNp73 had an OS rate of 77.8% (CI, 68.5%-88.4%) versus 96.6% (CI, 90%-100%). Through the ectopic expression of the genes of interest in NB4 and NB4-R2 cells (ATRA-sensitive and ATRA-resistant APL cell lines, respectively) we demonstrated that ΔNp73α and TAp73α are not important modulators of ATO-induced apoptosis. On the contrary, we detected that the expression of ΔNp73α blocked the increase in the expression of granulocytic differentiation markers CD11b and CD15 in NB4 cells treated with ATRA. Using a murine model, we observed that ectopic expression of ΔNp73α was associated with increased leukemic cell mass after ATRA treatment.Our analyzes on cell lines showed that ΔNp73α did not prevent the degradation of the PML-RARα oncoprotein and did not affect ATRA-induced nuclear body reorganization, but up-regulated the expression of the NANOG gene, a pluripotency transcription factor associated with cancer stem cell phenotype. We evaluated the proteome of our modified NB4 cells under ATRA-treated and untreated conditions. Differential analysis of protein abundance showed a greater number of proteins modulated by ΔNp73α than TAp73α in untreated NB4 cells. We found an upregulation of proteins involved in the RNA splicing process in NB4 cells with ectopic expression of ΔNp73α. ATRA treatment reversed regardless of the presence of p73 isoforms, suggesting that these pathways do not collaborate with ATRA resistance. Taken together, these results suggest that the ΔNp73α isoform reduces ATRA-induced myeloid differentiation using pathways other than PML-RARα degradation, and that the BMP4-ΔNp73α-NANOG axis could be involved in the regulation of this phenomenon.